(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2023)
The study area Lukshi and its environs is part of Dass sheet 149-SW, Bauchi state, Nothern Estaern Nigeria. Bounded by Latitudes 10º04’00"N and 9º59’00"N and longitudes 9º23’00"E and 9º22’00"E. Detailed geological mapping of the research area was carry out to update the previous geology information of the study area, the field observation indicates four lithological unite of Migmatite: Diatexite, Nebulite, Stromatic and Banded orthogneiss. Biotite, muscovite, quartz, feldspar are the major minerals seen during petrographic studies, and the migmatite showed little fractionations as they formed from medium temperature minerals to low temperature (Andesine to Oligoclase) coinciding with anorthoclase and microcline mineral assemblages at the discontinuous series arm of the Bowen reaction series. In variations diagrams, the compositional trends for the analyzed sample are characterized by negative correlation between TiO2, Fe2O3, MgO, CaO & P2O5 with increased SiO2 but positive correlation between Na2O, K2O and Al2O3 with increasing SiO2 even though some erratic and scattered distribution are also observed. The tectonic classifications of different authors indicated that the migmatite are peraluminous and peralkaline. They formed under syn-collision to late orogenic and anorogenic tectonic settings